The Duality Phenomenon in 1920-1930’s Small Prose of Vladimir Nabokov: Peculiarities of the Embodiment - Yurievna, Olga Osmukhina; Borisovich, Andrei Tanaseichuk; Petrovna, Svetlana Gudkova; Alexandrovna, Marina Trostina (Journal of History Culture and Art Research, 2019)
The article is devoted to the study of duality phenomenon in the texts of Vladimir Nabokov, its peculiarities and functioning. Investigation of the phenomenon helps to understand the interaction features between the author and his hero, the semantic content and the poetics of the text in a holistic unity. In the prose of V. Nabokov, the motive of duality is embodied through a split consciousness of the main characters. One of the main elements that accompany the bifurcation is the image of the mirror and the associated motive of mirroring (“Terror”, “Eavesdropper”, “Wing Kick”). The split often has a pronounced social character, when the consciousness of the hero creates exactly that double that is appropriate in a given situation (“Wing Kick, “Venetian”, “Eavesdropper”). Self-reflection of sick consciousness of the heroes most often ends in death for them (“Terra incognito”). In this case, the hero tries to become “different for others” (“Venetian”) or to hide his true face and intentions (“Eavesdropper”), or seeks to find a true “I”, and his own place in the world (“Pilgram”), but not endures the resistance of twins who pursue him (imaginary or real) and dies (“Wing kick”, “Pilgram”). In “Mashen’ka”, besides the split consciousness of the main character, caused by self-reflection, duality is expressed by the appearance of the counterpart-twins who repeat each other literally (Kolin-Gornotsvetov), antagonist-twins (Ganin-Alferov), and the split-image of Mashen’ka-Russia.